New insights into Chagas disease: a neglected disease in Latin America - Anna Von, Elisa Zaragoza, Danielle Jones, Alfonso J. Rodríguez-Morales, Carlos (The Journal of Infection in Developing Countries, 2007)
Like other neglected diseases, Chagas disease affects the daily lives of millions of people in Latin America and thereby hinders development in that region. A vector-borne disease that generates significant morbidity and mortality, Chagas disease is a major public health threat. In recent years, the changing epidemiological pattern of the disease and discoveries in its pathogenesis have renewed interest in this disease and have led to new approaches to its therapeutic management. In this article, we review these breakthroughs and suggest a more comprehensive approach to this neglected disease.